Stock Market Reaction to Short Sale Constraints : Empirical Evidence from Sectorial Performance of S&P/ASX 200 Index - Hakizimana, Axel (2011)
The primary objective of this study was to investigate the impact of short selling restrictions on different industries listed on the S&P/ ASX 200 in 2008. On 22nd September 2008, Australia followed the move of other developed countries and imposed a ban on short selling activities on all financial and non-financial stocks, because they were blamed to be responsible for the 2008 financial crisis. In the financial literature, it is argued that stock prices follow an upward movement when short selling activities are banned in a stock market. If short selling activities exist, investors will be able to react to unfavorable or negative information; hence stock prices will be biased upward. On the same time, there is another opinion which says that stock prices will follow a downward movement when short selling activities are not permitted. In fact, short selling activities reduce the speed of adjustment of stock prices towards negative information. The S&P/ASX 200 comprises several industry sectors. For that matter, the sample was divided into seven industries namely basic materials, communication, consumer, energy, financial, and utilities. Our empirical findings show strong evidence for the negative impact of short selling restrictions on basic materials, financial, and utilities sectors. This study is of capital importance to regulators because it showed that short selling restrictions affected key sectors of the Australian economy. Investors can learn from this study and construct portfolios containing best performing sectors which will increase their returns.